Molecular detection of malaria at delivery reveals a high frequency of submicroscopic infections and associated placental damage in pregnant women from northwest Colombia (2013)
ABSTRACT: Plasmodium infection in pregnancy causes substantial maternal and infant morbidity and mortality. In Colombia, both P. falciparum and P. vivax are endemic, but the impact of either species on pregnancy is largely unknown in this country. A cross-sectional study was carried out with 96 pregnant women who delivered at their local hospital. Maternal, placental, and cord blood were tested for malaria infection by microscopy and real-time quantitative polymerase chain reaction (qPCR). A high frequency of infection was detected by qPCR (45%). These infections had low concentrations of parasite DNA, and 79% were submicroscopic. Submicroscopic infections were associated with placental villitis and intervillitis. In conclusion, the overall frequency of Plasmodium infection at delivery in Colombia is much higher than previously reported. These data prompt a re-examination of the local epidemiology of malaria using molecular diagnostics to establish the clinical relevance of submicroscopic infections during pregnancy as well as their consequences for mothers and newborns.